Chronic exposure to yttrium induced cell apoptosis in the testis by mediating Ca2+/IP3R1/CaMKII signaling - Liu, Zhehao; Ding, Yechun; Xie, Shuchun; Hu, Yaqiong; Xiao, Hai; Liu, Xia; Fan, Xiaona (Frontiers in Public Health, 2023)
Introduction Environmental pollutants, such as rare earth elements, affect human health and particularly induce reproductive system injury. Yttrium (Y), one of the most widely used heavy rare earth elements, has been reported the cytotoxicity. However, the biological effects of Y3+ in the human body are largely unknown. Methods To further investigate the effects of Y on the reproductive system, in vivo (rat models) and in vitro studies were performed. Histopathological and immunohistochemical examination were conducted, and western blotting assays were performed to detect the protein expression. TUNEL/DAPI staining were used to detect cell apoptosis, and the intracellular calcium concentrations were also determined. Results Long-term exposure to YCl3 in rats produced significant pathological changes. YCl3 treatment could induce cell apoptosis in vivo and in vitro. In addition, YCl3 enhanced the concentration of cytosolic Ca2+ and up regulated the expression of IP3R1/CaMKII axis in Leydig cells. However, inhibition of IP3R1 and CaMKII with 2-APB and KN93, respectively, could reverse these effects. Conclusion Long-term exposure to yttrium could induce testicular injury by stimulating cell apoptosis, which might be associated with activation of Ca2+/IP3R1/CaMKII axis in Leydig cells.